European hours collected poems - Rudolf, Anthony 1942- (Carcanet Press Limited, 2017)
Now in his mid-seventies, distinguished poet, critic and translator Anthony Rudolf has amassed a lifetime's worth of work, presented here in this latest collection. For over five decades, Rudolf has weaved and nurtured literary connections between Britain and Europe, drawing on his Jewish heritage and affinity for Jewish, French and Russian culture to inform his poetry. A respected translator of the works of Yves Bonnefoy, Vigee, Jabes, Vinokourov and Tvardovsky, and the author of books of literary criticism on Primo Levi, Piotr Rawicz and others, Rudolf is truly an international writer and thinker, generous in his output and original in a conformist age
Keywords: English poetry / 20th century; English poetry / 21st century; Poésie anglaise / 20e siècle; Poésie anglaise / 21e siècle; English poetry; 1900-2099; Poetry; Poésie; Anthologie